PROFIL KECAKAPAN SOSIAL DAN PERSONAL SISWA DALAM HUBUNGANNYA DENGAN KECAKAPAN AKADEMIK PADA PEMBELAJARAN KIMIA - Latisma Dj; Mega Oktia Yoza; Jon Efendi (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Riau (UNRI), 2016)
The purpose of this research was to describe the life skills of students in learning chemistry and reveals the connections between life skills. The methods used in this research is descriptive research. The subject of research as much as 144 students of class XI in one of senior high school in the city of Padang. The selection of samples was conducted with stratified random sampling technique that divides students into 3 groups based on the level of their intelligence (IQ). Research data taken with observation, interview guidelines and tests of the student’s life skills. The results showed that the personal skills for students classified as well. The social skills of students is very good, students are able to manage their emotions very well, able to communicate well, has good interpersonal relationships, and understanding the other person very well. Student's academic prowess is quite good the ability of critical thinking, creative thinking, problem solving, and decision making students are on a category is good enough. The connection between life skills showed that a) there is a weak relationship between personal proficiency students with social skills among students with the values of the coefficients of correlation 0.33, b) there is a very weak relationship between students personal skills with the academic skills of students with the value of the correlation coefficient 0,004, and c) there is a very weak relationship between social skills among students with the academic skills of students with the value of the correlation coefficient 0,062.